Effect of Intraoperative Hypothermia on Post-anesthesia Recovery in Elderly Patients Undergoing Abdominal Surgery - Ahmed, Zulfikhar (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Intraoperative hypothermia (IOH) is a common concern in elderly patients undergoing abdominal surgery, potentially leading to prolonged recovery, increased post-operative complications, and extended hospital stays. Understanding the effects of hypothermia on recovery and patient comfort is crucial for improving surgical outcomes and optimizing healthcare resource utilization. Methods: The research investigates secondary data from peer-reviewed journals published between 2015 and 2024 to examine how IOH affects elderly patients during abdominal surgery. Medical research from PubMed and Scopus electronic databases led to data collection for studies that contained relevant clinical, along with physiological and psychological data. Results: The research shows that hypothermia during surgery directly affects treatment duration and complications, along with patient comfort and recovery time, as well as hospitalization lengths. Research has shown hypothermia disturbs temperature regulation and postpones anesthetic emergence and raises infection risk, and interferes with early rehabilitation decisions, which extend hospital duration. Discussion: In older abdominal surgery patients, IOH was repeatedly connected to delayed recovery, higher post-operative problems, discomfort, worse mobility, and longer hospital stays. The results underline the vital requirement of proactive perioperative warming techniques to guarantee patient safety and comfort as well as to enhance results. Conclusion: All surgical patients should maintain normal body temperature, but elderly patients especially need normothermic care to improve surgical recovery results. Controlling temperature through active methods, along with regular monitoring, helps minimize surgical complications and reduces hospital stay time because of its vital role in perioperative care.